2003
DOI: 10.1051/kmae:2003008
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Preference of Different Size Classes of Austropotamobius Pallipes in an Irish River

Abstract: Juvenile and immature crayfish are more difficult to find than adults and in consequence rather little is known about their habitat preferences. Smaller crayfish are able to inhabit different areas within the stream compared to adult crayfish. Whereas adult crayfish occur under stones and cobble in the river, juveniles and small individuals may be found along the margins, among rootlets and vegetation. A survey was carried at two sites in the Liffey catchment (Ireland) to assess habitat preference of crayfish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 18 publications
0
12
1
Order By: Relevance
“…Gherardi et al 1996;Grandjean et al 1998Grandjean et al , 2000Grandjean et al , 2003Largiarder et al 2000;Demers et al 2003;Trouilhe et al 2003;Fratini et al 2005). This provides enough information to preserve this species in situ.…”
Section: Introductionmentioning
confidence: 99%
“…Gherardi et al 1996;Grandjean et al 1998Grandjean et al , 2000Grandjean et al , 2003Largiarder et al 2000;Demers et al 2003;Trouilhe et al 2003;Fratini et al 2005). This provides enough information to preserve this species in situ.…”
Section: Introductionmentioning
confidence: 99%
“…SCHULZ and KIRCHLEHNER (1984) showed that A. torrentium abundance was correlated to the relative amount of stones and pieces of wood, serving as shelter for this crayfish. DEMERS, REYNOLDS and CIONI, (2004) investigated habitat preference of different size classes of A. pallipes in an Irish River. Whereas adult crayfish occur under stones and cobble in the river, smaller individuals may be found along the margins, among rootlets and vegetation (SMITH et al, 1996;REYJOL and ROQUEPLO, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Decapods are easy to recognise, individuals are a suitable size to pinpoint and handle, they can be handled without harming the animal and are not dangerous for interested people, either. Another advantage of this animal group is that many crayfish species are widespread, not only existing in some remote reserves, and they also occur in different habitat types (DEMERS et al, 2003). They have a hard shell, too, containing distinguishing structures for identification, and thus useful pictures can also be made from remains.…”
Section: Discussionmentioning
confidence: 99%